Source decomposition of the frontocentral auditory steady‐state gamma band response in schizophrenia patients and healthy subjects - Koshiyama, Daisuke; Miyakoshi, Makoto; Joshi, Yash B.; Nakanishi, Masaki; Tanaka‐Koshiyama, Kumiko; Sprock, Joyce; Light, Gregory A. (Psychiatry and clinical neurosciences, 2021)
Aim Gamma‐band auditory steady‐state response (ASSR) is a neurophysiologic index that is increasingly used as a translational biomarker in the development of treatments of neuropsychiatric disorders. While gamma‐band ASSR is generated by distributed networks of highly interactive temporal and frontal cortical sources, the majority of human gamma‐band ASSR studies using electroencephalography (EEG) highlight activity from only a single frontocentral scalp site, Fz, where responses tend to be largest and reductions in schizophrenia patients are most evident. However, no previous study has characterized the relative source contributions to Fz, which is a necessary step to improve the concordance of preclinical and clinical EEG studies. Methods A novel method to back‐project the contributions of independent cortical source components was applied to assess the independent sources and their proportional contributions to Fz as well as source‐resolved responses in 432 schizophrenia patients and 294 healthy subjects. Results Independent contributions of gamma‐band ASSR to Fz were detected from orbitofrontal, bilateral superior/middle/inferior temporal, bilateral middle frontal, and posterior cingulate gyri in both groups. In contrast to expectations, the groups showed comparable source contribution weight to gamma‐band ASSR at Fz. While gamma‐band ASSR reductions at Fz were present in schizophrenia patients consistent with previous studies, no group differences in individual source‐level responses to Fz were detected. Conclusion Small differences in multiple independent sources summate to produce scalp‐level differences at Fz. The identification of independent source contributions to a single scalp sensor represents a promising methodology for measuring dissociable and homologous biomarker targets in future translational studies.